Innovation as a Bridging Mechanism Between Behavioral Theory and Sustainable Entrepreneurship: A Bibliometric Analysis of the Indonesian Research Landscape - Danang Kusnanto; Suryana; Chairul Furqon; Mokh Adib Sultan (Journal of Economic Education and Entrepreneurship Studies, 2026)
This study examines the integration of behavioral theory and sustainable entrepreneurship by positioning innovation as a conceptual connecting mechanism. This topic is important due to the growing demand for global sustainability and the need for a synthesis between psychological determinants and sustainability-oriented entrepreneurial practices. Although behavioral theory, particularly intention-based models, is widely used in entrepreneurship studies, its integration with sustainable entrepreneurship remains fragmented, with a focus on intentions rather than actual behavior. This study offers a new conceptual synthesis by mapping innovation as a structural bridge between behavioral determinants and sustainable entrepreneurship outcomes, an area that has not been systematically explored in the previous literature. The study employed a Scopus-based bibliometric analysis, employing a keyword co-occurrence approach in VOSviewer to identify thematic clusters, network structures, and knowledge convergence patterns. The results revealed four main clusters: behavioral theory, entrepreneurial intention, technology adoption, and sustainable entrepreneurship, with innovation as the main connecting node. The literature is still dominated by intention-based approaches. These findings emphasize the need to develop an integrative model that explains the transformation of behavioral determinants into sustainable entrepreneurship through innovation and provide directions for further empirical research.